The Simple Script Wrapper for OpenMI: Enabling interdisciplinary modeling studies - Bulatewicz, Tom; Allen, A.; Peterson, Jeffrey M.; Staggenborg, Scott A.; Welch, Stephen M.; Steward, David R. (My University, 2013)
Integrated environmental modeling enables the development of comprehensive simulations by compositing individual models within and across disciplines. The Simple Script Wrapper (SSW), developed here, provides a foundation for model linkages and integrated studies. The Open Modeling Interface (OpenMI) enables model integration but it is challenging to incorporate scripting languages commonly used for modeling and analysis such as MATLAB, Scilab, and Python. We have developed a general-purpose software component for the OpenMI that simplifies the linking of scripted models to other components. Our solution enables scientists to easily make their scripting language code linkable to OpenMI-compliant models fostering collaborative, interdisciplinary integrated modeling. The simplicity afforded by our solution is presented in a case study set in the context of irrigated agriculture. The software is available online as supplementary material and includes an example that may be followed to employ our methods.
Keywords: OpenMI; Interdisciplinary modeling; Scripting languages; Model integration; Integrated modeling